New Freshwater Gomphonemoid Diatoms from Streams in the Sierra Nevada Mountains, California, USA - Stancheva, Rosalina; Sheath, Robert G.; Kociolek, J. Patrick (Phytotaxa, 2016)
Light and scanning electron microscopic observations of three new species of freshwater gomphonemoid diatoms are presented from mountain streams in California: Gomphonema californicum sp. nov., Gomphonema sierrianum sp. nov., and Gomphoneis oreophila sp. nov. Two of the species have morphological novelties related to the structure of the areolae, which are discussed in comparison with similar taxa. Gomphonema californicum shows a variety of areolar morphologies (i.e. lineola-like, c-shaped, and circular) within a single uniseriate stria. Unique to Gomphoneis oreophila, a member of the Herculeana subgroup, are the uniform areolae with circular openings without apparent occlusions. All of these species are distributed in remote streams of the Sierra Nevada Mountains of California, suggesting there are still new species to be found in this biodiversity-rich region.